The significance of the religious factor in the internal and external policies of Turkey - Michalak. Ryszard (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The author of the article undertakes an attempt to establish the reasons and manifestations of the increased importance of the religious factor in the policy of contemporary Turkey, as well as to capture the transformations taking place in Turkish religious policy. The author believes that the last-mentioned process strictly corresponds to the phenomena of withdrawal from the model of nonreligious autocracy which was one of the main characteristics of Kemalism in favour of the model of a country which is de facto religious. This, in turn, becomes the emblem of Neoosmanism.
Keywords: Turkey; Turkish Confessional Policy; domestic politics; foreign policy; Islamic nationalism; state and religion; the Middle East; Diyanet; Kemalism; Erdoganism; Sunniism; religious minority